Design, synthesis and anti-breast cancer evaluation of biaryl pyridine analogues as potent RSK inhibitors. (1st March 2022) - Cui, Yi-Man; Li, Wei; Shen, Tian-Ze; Tao, Yong-Xing; Liu, Biao-Qi; Li, Xiao-Li; Zhang, Rui-Han; Jiang, De-Wei; Xiao, Wei-Lie
Graphical abstract: Highlights: Discovery of potent biaryl pyridine analogues and the most active RSK inhibitor was compound 7d, which shows similar RSK inhibitory efficacy to the lead compound LJH685. Except for 7d, the compounds with higher activity all carry a benzyl group. Molecular docking results show that 7d validates our molecular design. Preliminary SAR and molecular models of selected compounds are studied. Abstract: In order to discover and develop the new RSK kinase inhibitor, 50 pyridyl biaryl derivatives were designed and synthesized with LJH685 as the lead compound and their anti-tumor ability was tested. The results showed that the ability of 7d compound to inhibit the phosphorylation of YB-1 was comparable to that of LJH685. Among them, after preliminary screening, compound 7d showed good activity in inhibiting cell proliferation. Therefore, we took 7d as an example and performed molecular docking analysis on it. Judging from the overlapping combination diagram with LJH685, the results have verified that compound 7d has a similar skeleton to LJH685 and has a similar docking effect with RSK. Therefore, compound 7d is in line with the RSK inhibitor we designed and could be developed to a promising anti-tumor drug in the future.